Association of BRCA1/2 mutations with ovarian cancer prognosis: An updated meta-analysis. Issue 2 (January 2018) - Huang, Yong-Wen
Abstract: Objective: A meta-analysis was performed to determine if BRCA1/2 mutations are associated with improved overall survival (OS) and progression-free survival (PFS) in patients with ovarian cancer. Research design and methods: Studies of patients with primary or recurrent ovarian cancer that examined the relationship between BRCA1/2 mutation status and outcomes were included. Main outcome measures: The primary outcomes were OS and PFS of patients with and without BRCA1 and BRCA2 mutations. The secondary outcome was treatment response: complete response, partial response, and overall response. Results: Overall analysis revealed BRCA1/2 mutations were associated with improved OS [hazard ratio (HR) = 0.75; 95% confidence interval (CI): 0.64, 0.88; P < .001] and PFS (HR = 0.80; 95% CI: 0.64, 0.99; P = .039). BRCA1 mutations were significantly associated with improved OS (HR = 0.75) but not PFS, and BRCA2 mutations alone were not associated with either improved OS or PFS. The presence of BCRA1/2 mutations was associated with a better overall response rate, higher complete response rate, and lower partial response rate; however, BRCA1 or BRCA2 alone was not associated with overall response rate. Conclusions: BRCA1 mutations appear to be associated with improved OS in patients with ovarian cancer. However, the effect of BRCA1 mutations on PFS and BRCA2 mutations alone on OS and PFS is less clear. Abstract : Supplemental Digital Content is available in the text